Female Labor Supply with a Discontinuous, Nonconvex Budget Constraint: Incorporation of a Part-Time/Full-Time Wage Differential - Averett, Susan L.; Hotchkiss, Julie L. (The Review of Economics and Statistics, 1997)
This paper incorporates the well-documented part-time/full-time wage differential into an empirical labor supply model with both a heterogeneity- and a random-error term and estimates that model for women in the United States. Incorporation of the part-time/full-time wage differential results in a unique discontinuous, nonconvex budget set, and the consideration of estimation procedures previously unconfronted in the nonlinear budget constraint literature. The full structural representation of the budget constraint is shown to “fit” better than the alternative models estimated, and to yield a predicted hours distribution representative of actual hours.